"Forget to Whom You Have Told This Proverb": Directed Forgetting of Destination Memory in Alzheimer's Disease. (30th March 2015) - El Haj, Mohamad; Gandolphe, Marie-Charlotte; Allain, Philippe; Fasotti, Luciano; Antoine, Pascal
Abstract : Destination memory is the ability to remember the receiver of transmitted information. By means of a destination memory directed forgetting task, we investigated whether participants with Alzheimer's Disease (AD) were able to suppress irrelevant information in destination memory. Twenty-six AD participants and 30 healthy elderly subjects were asked to tell 10 different proverbs to 10 different celebrities (List 1). Afterwards, half of the participants were instructed to forget the destinations (i.e., the celebrities) whereas the other half were asked to keep them in mind. After telling 10 other proverbs to 10 other celebrities (List 2), participants were asked to read numbers aloud. Subsequently, all the participants were asked to remember the destinations of List 1 and List 2, regardless of the forget or remember instructions. The results show similar destination memory in AD participants who were asked to forget the destinations of List 1 and those who were asked to retain them. These findings are attributed to inhibitory deficits, by which AD participants have difficulties to suppress irrelevant information in destination memory.